An Importance of Magnesium Deficiency in the Formation of Vegetative Disadaptation in Children and Adolescents with Digestive Tract Pathology - Boiarska, L. M.; Gorbachova, S. V.; Potapenko, S. V. (Zaporozhye Medical Journal, 2015)
Aim. In the study of magnesium deficiency, a distinction is made between magnesium hypoelementosis and magnesium deficit. As a result, detection of the magnesium deficiency and its influence on vegetative disadaptation progression can help to correct damages in early stages and to decrease frequency of chronization of digestive tract disorders in children. Methods and results. 48 children at the ages from 7 to 17 years with complaints on sickliness, stomachache, dyspeptic symptoms were under the care. The first group contained of 28 children with organic digestive system disorders, the second – 20 children with functional digestive system disorders. In both groups serum and intracellular concentration of Mg, Holter monitoring of ECG were carried out. Conclusion. Among children and adolescents with digestive tract pathology, 4,3% of patients had magnesium deficit. Hypoelementosis was detected in 18,7% of cases, that demonstrates great prevalence of latent magnesium deficiency and the necessity of the intracellular content study. Indices of both intracellular (p≤0,05) and extracellular (p ≤0,001) magnesium in children from the 1st group were much lower than in children from the 2nd group. This demonstrates mutual influence of organic digestive tract pathology and magnesium deficit on the development and severity of pathologies. Direct and strong correlation line between intracellular magnesium level lowering and lowered indices of HRV time-line analysis was detected in the 1st group. Correlation absence in the 2nd group demonstrates the influence of magnesium deficiency on vegetative disadaptation development and provides change of digestive tract functional disorders to organic.